2012
DOI: 10.1175/mwr-d-11-00208.1
|View full text |Cite
|
Sign up to set email alerts
|

An Orography-Associated Extreme Rainfall Event during TiMREX: Initiation, Storm Evolution, and Maintenance

Abstract: This study investigates a long-duration mesoscale system with extremely heavy rainfall over southwest Taiwan during the Terrain-influenced Monsoon Rainfall Experiment (TiMREX). This mesoscale convective system develops offshore and stays quasi-stationary over the upstream ocean and southwest coast of Taiwan. New convection keeps developing upstream offshore but decays or dies after moving into the island, dropping the heaviest rain over the upstream ocean and coastal regions. Warm, moist, unstable conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
96
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 52 publications
3
96
0
Order By: Relevance
“…However, toward lower latitudes such as the subtropics and tropics, the environments may be less conducive to cold pool development (e.g., Tompkins, 2001). Some studies of extreme rainfall events in South China and Taiwan have shown that surface-based cold air produced by previous convection that had dissipated for hours or even in the day before, when impinged by the moist monsoonal flow, in particular the lowlevel jet (LLJ), can act to trigger new convection in succession (e.g., Zhang and Zhang, 2012;Xu et al, 2012;C.-C. Wang et al, 2014a;Luo et al, 2014). Such influences of "cold domes," however, are different from the lifting at gust fronts produced by coexisting, dissipating cells or those that had just dissipated, and the induced MCSs may be less organized if a linear forcing such as a front or low-level convergence zone is absent (e.g., Xu et al, 2012;C.-C. Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…However, toward lower latitudes such as the subtropics and tropics, the environments may be less conducive to cold pool development (e.g., Tompkins, 2001). Some studies of extreme rainfall events in South China and Taiwan have shown that surface-based cold air produced by previous convection that had dissipated for hours or even in the day before, when impinged by the moist monsoonal flow, in particular the lowlevel jet (LLJ), can act to trigger new convection in succession (e.g., Zhang and Zhang, 2012;Xu et al, 2012;C.-C. Wang et al, 2014a;Luo et al, 2014). Such influences of "cold domes," however, are different from the lifting at gust fronts produced by coexisting, dissipating cells or those that had just dissipated, and the induced MCSs may be less organized if a linear forcing such as a front or low-level convergence zone is absent (e.g., Xu et al, 2012;C.-C. Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…WSTRs caused by the easterly reflux, especially the strong southwest monsoon burst, are directly influenced by low-level processes in the PBL [3]. WSTRs could be triggered by other mesoscale processes within the PBL caused by the mesoscale convective system (e.g., [4][5][6]) and the mesoscale vortex [7][8][9], as well as orographic effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have improved our understanding of mechanisms related to orographically induced precipitation systems, examining factors such as low-level convergence, wind blocking (measured by the Froude number, Fr 0U/Nh, where U is the averaged wind speed at altitudes less than that of the maximum terrain height, h is the maximum terrain height and N is the BruntÁVaisala frequency), ambient wind direction and speed, terrain steepness and environmental stability induced by various sizes and shapes of terrains (Smith, 1979;Smolarkeiwicz et al, 1988;Smolarkeiwicz and Rotunno, 1989;Li et al, 1997;Olafsson, 2000;Chiao and Lin, 2003;Jiang, 2003;Petersen et al, 2003;Reeves and Lin, 2007;Houze, 2012;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a moist environment, a previously generated precipitation system approaching a mountainous region is significantly enhanced in the vicinity of the terrain due to flow modification. Although many studies have examined precipitation systems in mountainous regions, the effects of terrain on pre-existing precipitation systems approaching a terrain with a moist environment are relatively unexplored, and most previous studies have focussed on the Taiwan region (Lin et al, 1992;Jou and Deng, 1998;Chen et al, 2001;Wang et al, 2005;Reeves and Lin, 2007;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%